ENHANCING STUDENTS’ IMAGINATION AND EMOTIONAL EXPERIENCE THROUGH PAINTING - Boboqulova Adiba Husanovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores how painting can enhance students’ imagination and emotional experiences within the educational process. Painting allows learners toexpress personal feelings, explore creativity, and develop visual and emotional literacy. Through interaction with colors, forms, and compositions, students expand their imagination and gain a deeper understanding of their own emotions and those of others. The article highlights methods for integrating painting into lessons to foster both cognitive and emotional growth, demonstrating its significance as an educational tool that develops creativity, empathy, and aesthetic appreciation.